THE EFFECT OF GOOD CORPORATE GOVERNANCE (GCG) IMPLEMENTATION ON EARNINGS QUALITY AND ITS IMPACT ON CORPORATE SUSTAINABILITY (AN EMPIRICAL STUDY OF INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE, 2019–2022) - Hadnan, Muhamad (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This study was prompted by phenomena observed at PT. Waskita Karya (Persero) Tbk and PT Wijaya Karya (Persero) Tbk. The study aims to examine the effect of implementing good corporate governance mechanisms on earnings quality and its impact on corporate sustainability. The population consists of infrastructure companies listed on the Indonesia Stock Exchange from 2019 to 2022. The data used is secondary data, with a sampling technique employing purposive sampling; 27 samples were obtained from 65 sample criteria. The analysis in this study uses a panel data regression model with the assistance of the EViews 10 program. The results of the study indicate that institutional ownership, managerial ownership, independent directors, audit committees, and auditor quality do not have a significant effect on earnings quality. The results of this study also indicate that institutional ownership, managerial ownership, and independent directors have a significant effect on earnings quality, whereas audit committees, auditor quality, and earnings quality do not have a significant effect on firm sustainability. Earnings quality was also found not to be a mediating variable between institutional ownership, managerial ownership, independent directors, audit committees, and auditor quality on corporate sustainability.